Antioxidant and inhibitory activities of α-Amylase, α-Glucosidase and Angiotensin-I of protein hydrolysates from “Sac-Beh” quality protein maize (QPM) - Jiménez Suaste, Nidia Isabel; Chel-Guerrero, Luis; Betancur- Ancona, David; Bustillos, Roberto Zamora (Emirates Journal of Food and Agriculture, 2023)
Diabetes and hypertension are health problems with high mortality rates. Protein hydrolysates with antidiabetic and antihypertensive potential are suitable for making functional foods that could lower blood glucose and blood pressure, improve insulin absorption, and inhibit the enzymes involved in the development of these diseases. The protein hydrolysis was realized using Alcalase®, Flavourzyme®, and the sequential system Alcalase®-Flavourzyme®. The inhibitory activity, antioxidant activity, and ACE-1, α-Amylase, α-Glucosidase enzymes of protein hydrolysates derived from QPM Sac-Beh Zea mays L. were evaluated by in vitro assays. The hydrolysates with the highest degree of hydrolysis (90 min) were used to evaluate bioactivity. The maximum values for antioxidant assays were 9.1 Trolox equivalents/mg protein for Alcalase®-Flavourzyme®, 45.51% decolorization of 2,2-diphenyl-1-picrylhydrazyl (DPPH); the inhibition of α-Amylase with the Alcalase® system was 45.84%, for α-Glucosidase was 64.3% for the Flavourzyme® system; the IC value for the mean concentration of ACE-I enzyme activity with the Alcalase®-Flavourzyme® system was 73.09μg/ml with a percentage inhibition of 69.06%. Hydrolysates from the Sac-Beh variety of quality protein maize (QPM) could be used in the elaboration of pharmaceutical or functional foods that work as adjuvants in the treatment of people with hypertension, type II diabetes mellitus, as well as antioxidants. Keywords: Maize; Diabetes; Hypertension; Protein hydrolysates; Sac-Beh; Angiotensin-I